Exploring user satisfaction for e-learning systems via usage-based metrics and system usability scale analysis. (August 2016) - Harrati, Nouzha; Bouchrika, Imed; Tari, Abdelkamel; Ladjailia, Ammar
Abstract: The use of e-learning technology is incontestably recognized as an important and integral part of the educational process. Considerable research studies are carried out in order to apprehend how effective and usable e-learning systems. In this paper, an empirical-based study is conducted to explore how lecturers interact with an e-learning environment based on a predefined task model describing low-level interactions. Client-side log data is collected from university lecturers from the Electrical and Computer Science departments. Subsequently, data analysis is conducted to infer the usability degree from the estimated usage metrics together with further exploratory analysis from user feedback via System Usability Scale. Experimental results reveal that the System Usability Scale score is not a sufficient measure to express the true acceptance and satisfaction level of lecturers for using the e-learning systems. The evaluation must be fulfilled in tandem with analyzing the usage metrics derived from interaction traces in a non-intrusive fashion. The proposed approach is a milestone towards usability evaluation to improve the acceptance and user experience for academic staff and students. Highlights: Usage Metrics can offer better insights for usability assessment of software systems. Age and academic qualification can affect the degree of usability. Experiments revealed that gender has no influence on the perceived ease of use. Subjective Measurements should be used in tandem with usage metrics.